An inorganic–organic hybrid photochromic material with fast response to hard and soft X-rays at room temperature. Issue 36 (15th March 2018) - Guo, Pei-Yu; Sun, Cai; Zhang, Ning-Ning; Cai, Li-Zhen; Wang, Ming-Sheng; Guo, Guo-Cong
Abstract : The first X-ray-induced photochromic material, with the coloration time being within 5 min when exposed to Mo-Kα and Al-Kα X-rays, was designed and synthesized. Abstract : A photochromic compound with fast response to Mo-Kα (4 min) and Al-Kα (1 s) X-rays was synthesized using a cluster of high- Z atoms and a flexible viologen zwitterion. The coloration time of 1 s when exposed to soft X-rays is the recorded minimum for X-ray-induced photochromic materials, indicating a potential to detect low-energy X-rays.